Liquid crystal polymer compositions, articles and methods of manufacture
Patent Information
- Application Number
- JP2023525024
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-08
- Filing Date
- 2021-10-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-10-21
AI Technical Summary
As power density increases in electrical components, such as electric vehicle motors, heat storage becomes a significant issue, reducing efficiency and requiring improved thermal management solutions.
A polymer composition comprising liquid crystal polymer (LCP), flat glass fibers, and boron nitride and/or zinc oxide, with specific weight percentages, enhancing thermal conductivity and mechanical properties.
The composition achieves improved thermal conductivity and mechanical strength, effectively managing heat in high-power density applications while maintaining structural integrity.
Abstract
Description
[Technical Field]
[0001] Related applications This application claims priority to U.S. Patent No. 63 / 105416 filed on 26 October 2020 and European Patent No. 21150658.9 filed on 8 January 2021, the entire contents of each of these applications being incorporated herein by reference for all purposes.
[0002] A polymer composition is provided. The polymer composition has excellent thermal conductivity and comprises liquid crystal polymer ("LCP"), flattened glass fibers, and either or both of boron nitride and zinc oxide. Articles into which the polymer composition is introduced, as well as methods for manufacturing the polymer composition and the article, are also provided. [Background technology]
[0003] When the power density of an electrical component increases, the thermal output of the electrical component also increases, at least in part due to the resistance of the current carriers. The result is a significantly increased heat storage in the electrical component. For example, with the increasing consumer demand for vehicles with higher performance, there is a continuously growing need to increase the power density of electric motors for electric vehicles (e.g., automobiles, motorcycles, ships, and airplanes). However, when power density increases, heat storage in and around the electric motor also increases, which can significantly reduce motor efficiency. [Overview of the project]
[0004] In a first embodiment, a polymer composition is provided comprising a liquid crystal polymer ("LCP") formed from the polycondensation of the following monomers: terephthalic acid, an aromatic diol, a first aromatic dicarboxylic acid, and an aromatic hydrocarboxylic acid; 10% to 40% by weight of flattened glass fibers; and boron nitride and / or zinc oxide, with a total concentration of boron nitride and zinc oxide of 15% to 50% by weight. In some embodiments, the aromatic diol is 4,4'-biphenol, the aromatic hydrocarboxylic acid is 4-hydroxybenzoic acid, and the first aromatic dicarboxylic acid is isophthalic acid.
[0005] In some embodiments, the polymer composition does not contain zinc oxide. In some embodiments, the polymer composition does not contain boron nitride. In some embodiments, the polymer composition contains boron nitride and zinc oxide. In one such embodiment, the relative concentration of boron nitride to zinc oxide is 0.5 to 2.
[0006] In some embodiments, the polymer composition has a through-plane thermal conductivity of 0.20 W / mK to 0.9 W / mk as measured according to ASTM E1461-13. In some embodiments, the polymer composition has a bending strength of 100 MPa to 250 MPa as measured according to ASTM D790. In some embodiments, the polymer composition has a bending strain of 100 MPa to 190 MPa as measured according to ASTM D790. In some embodiments, the polymer composition has a bending strain of 100 MPa to 190 MPa as measured according to ASTM D3835. -1 Shear rates of 90 Pa·s to 300 Pa·s; 500 s -1 Shear rates of 35 Pa·s to 150 Pa·s, or 1000 s -1 It has an apparent viscosity of 25 Pa·s to 100 Pa·s at shear rates.
[0007] In some embodiments, the polymer composition does not contain circular glass fibers.
[0008] In another embodiment, an article comprising a polymer composition, which is an electrical component, is provided. In some embodiments, the article is an electric motor component. In some embodiments, the article is a slot liner. In some embodiments, the article is selected from the group consisting of automotive parts, aerospace parts, and marine parts. [Modes for carrying out the invention]
[0009] Polymer compositions comprising at least 20% by weight of liquid crystal polymer ("LCP"), 10% to 40% by weight of flattened glass fibers, and 15% to 50% by weight of boron nitride and / or zinc oxide are described herein. It has been surprisingly found that polymer compositions containing LCP in combination with flattened glass fibers and boron nitride and / or zinc oxide have improved thermal conductivity and flexural properties compared to similar polymer compositions having round glass fibers instead of flattened glass fibers. Wherein use herein, wt.% refers to the total weight of the polymer composition unless otherwise specified.
[0010] Even if any description is made in relation to a specific embodiment, it is applicable to and interchangeable with other embodiments of the present disclosure, and where it is said that an element or component is included in and / or selected from a list of enumerated elements or components, in relevant embodiments expressed in this application, the element or component may also be any one of the individual enumerated elements or components, or may be selected from any group of two or more of the explicitly listed elements or components; any element or component enumerated in a list of elements or components may be omitted from such list; any enumeration of numerical ranges by endpoint in this specification includes all numerical values included in the enumerated range, as well as the endpoints of the range and their equivalents. Unless otherwise specifically limited, the terms “alkyl” and its derivatives such as “alkoxy,” “acyl,” and “alkylthio,” as used herein, include linear, branched, and cyclic portions. Examples of alkyl groups are methyl, ethyl, 1-methylethyl, propyl, 1,1-dimethylethyl, and cyclopropyl.
[0011] Unless otherwise specifically stated, each alkyl and aryl group may be unsubstituted, or may be substituted with one or more substituents selected from halogen, hydroxyl, sulfo, C1-C6 alkoxy, C1-C6 alkylthio, C1-C6 acyl, formyl, cyano, C6-C15 aryloxy, or C6-C15 aryl, provided that the substituents are sterically compatible and the rules of chemical bonding and strain energy are satisfied. The term "halogen" or "halo" includes fluorine, chlorine, bromine, and iodine, with fluorine being preferred.
[0012] Similarly, unless specifically limited, the term “aryl” refers to a phenyl, indanyl, or naphthyl group. An aryl group may contain one or more alkyl groups, in which case it may be called an “alkylaryl” group; for example, it may consist of an aromatic group and two C1-C6 groups (e.g., methyl or ethyl). An aryl group may also contain one or more heteroatoms, for example, N, O, or S, in which case it may be called a “heteroaryl” group; these heteroaromatic rings may condense with other aromatic systems. Such heteroaromatic rings include, but are not limited to, furanyl, thienyl, pyrrolyl, pyrazolyl, imidazolyl, triazolyl, isoxazolyl, oxazolyl, thiazolyl, isothiazolyl, pyridyl, pyridazyl, pyrimidyl, pyrazinyl, and triazinyl ring structures. The aryl or heteroaryl substituent may be unsubstituted, or may be substituted with one or more substituents selected from, but not limited to, halogens, hydroxyls, C1-C6 alkoxys, sulfosulfos, C1-C6 alkylthios, C1-C6 acyls, formyls, cyanos, C6-C15 aryloxys, or C6-C15 aryls, provided that the substituents are sterically compatible and the rules for chemical bonding and strain energy are satisfied.
[0013] Polymer composition The polymer composition contains LCP, 10% to 40% by weight of flattened glass fibers, and 15% to 50% by weight of boron nitride and / or zinc oxide. Remarkably, the polymer composition containing LCP along with the combination of flattened glass fibers and boron nitride and / or zinc oxide exhibits improved thermal conductivity and flexural properties compared to similar polymer compositions having round glass fibers instead of flattened glass fibers. Furthermore, in some embodiments, the polymer composition had a particularly desirable apparent viscosity for injection molding of thin-walled articles.
[0014] The polymer composition exhibited remarkably improved thermal conductivity. As described above, there is a significantly increased thermal output, particularly in high-power-density electrical component applications (e.g., electric motors for electric vehicles), which leads to heat accumulation within and around the electrical component. Consequently, improved cooling is necessary. The polymer compositions described herein have significantly improved thermal conductivity that helps conduct heat from electric motor components. Of course, the same applies to any article (e.g., power supplies) that carries a considerable current or has high power density requirements. In some embodiments, the polymer composition has a through-plane thermal conductivity of at least 0.20 watts / meter Kelvin ("W / mK"), at least 0.25 W / mK, at least 0.3 W / mK, at least 0.35 W / mK, at least 0.4 W / mK, at least 0.45 W / mK, at least 0.5 W / mK, at least 0.55 W / mK, or at least 0.6 W / mK. In some embodiments, the polymer composition has a per-plane thermal conductivity of 0.9 W / mK or less or 0.85 W / mK or less. In some embodiments, the polymer composition has a per-plane thermal conductivity of 0.2 W / mK to 0.9 W / mK, 0.25 W / mK to 0.9 W / mK, 0.3 W / mK to 0.9 W / mK, 0.35 W / mK to 0.9 W / mK, 0.4 W / mK to 0.9 W / mK, 0.45 W / mK to 0.9 W / mK, 0.5 W / mK to 0.9 W / mK, 0.55 W / mK to 0.9 W / mK, or 0.6 W / mK to 0.9 W / mK. In some embodiments, the polymer composition has a through-plane thermal conductivity of 0.2 W / mK to 0.85 W / mK, 0.25 W / mK to 0.85 W / mK, 0.3 W / mK to 0.85 W / mK, 0.35 W / mK to 0.85 W / mK, 0.4 W / mK to 0.85 W / mK, 0.5 W / mK to 0.85 W / mK, 0.55 W / mK to 0.85 W / mK, or 0.6 W / mK to 0.85 W / mK. The through-plane thermal conductivity can be measured as described in the Examples section.
[0015] Also, the polymer composition exhibited enhanced bending properties. In some embodiments, the polymer composition has a tensile strength at break (referred to as "tensile strength") of 100 MPa to 250 MPa, 120 MPa to 250 MPa, 130 MPa to 250 MPa, 140 MPa to 250 MPa, or 150 MPa to 250 MPa. In some embodiments, the polymer composition has a tensile strength of 100 MPa to 250 MPa, 120 MPa to 220 MPa, 130 MPa to 220 MPa, 140 MPa to 220 MPa, or 150 MPa to 220 MPa. In some embodiments, the polymer composition has a tensile strength of 100 MPa to 200 MPa, 120 MPa to 200 MPa, 130 MPa to 200 MPa, 140 MPa to 200 MPa, or 150 MPa to 200 MPa. In some embodiments, the polymer composition has a tensile strength of 100 MPa to 190 MPa, 120 MPa to 190 MPa, 130 MPa to 190 MPa, 140 MPa to 190 MPa, or 150 MPa to 190 MPa. In some embodiments, the polymer composition has a tensile strain at break (referred to as "tensile strain") of 1% to 3%, 1.5% to 3%, or 1.8% to 3%. In some embodiments, the polymer composition has a tensile strain of 1% to 2.5%, 1.5% to 2.5%, or 1.8% to 2.5%. The tensile strength and tensile elongation can be measured as described in the Examples section.
[0016] In some embodiments, the polymer composition is 100 seconds -1 , (referred to as "s -1 ") and has an apparent viscosity (referred to as "η") of 90 Pa·s to 300 Pa·s, 120 Pa·s to 300 Pa·s, or 150 Pa·s to 300 Pa·s at a shear rate of. In some embodiments, the polymer composition has an η of 90 Pa·s to 250 Pa·s, 120 Pa·s to 250 Pa·s, or 150 Pa·s to 250 Pa·s at a shear rate of 100 s -1 . In some embodiments, the polymer composition is 500 s -1has an η of 35 Pa·s to 150 Pa·s, 70 Pa·s to 150 Pa·s, 35 Pa·s to 120 Pa·s, or 70 Pa·s to 120 Pa·s at a shear rate of. In some embodiments, the polymer composition is 1000 s -1 has an η of 25 Pa·s to 100 Pa·s, 50 Pa·s to 100 Pa·s, 25 Pa·s to 90 Pa·s, or 50 Pa·s to 90 Pa·s at a shear rate of -1 . η can be measured as described in the Examples section.
[0017] In some embodiments, the polymer composition has a melting temperature (“Tm”) of at least 300 °C, at least 320 °C, or at least 340 °C. In some embodiments, the polymer composition has a Tm of 430 °C or less, 410 °C or less, or 400 °C or less. In some embodiments, the polymer composition has a Tm of 300 °C to 430 °C, 320 °C to 410 °C, or 340 °C to 400 °C. Tm can be measured according to ASTM D3418.
[0018] Liquid crystal polymer The LCP is formed from the polycondensation of the following monomers: terephthalic acid, aromatic diol, a first aromatic dicarboxylic acid different from terephthalic acid, and aromatic hydroxycarboxylic acid. In some embodiments, at least one of the first aromatic dicarboxylic acid and the aromatic hydroxycarboxylic acid does not contain a naphthyl group.
[0019] In some embodiments, the aromatic diol is from the group of the following formulas: HO-Ar1-OH, and (1) HO-Ar2-T1-Ar3-OH, (2) (wherein Ar1 to Ar3 are independently selected from one or more substituents selected from the group consisting of halogen, C1 to C 15 alkyl (akyl), and C6 to C 15 aryl, and are optionally substituted with one or more substituents selected from the group consisting of aryl groups; T1 is selected from the group consisting of a bond, O, S, -SO2-, -C(=O)-, and C1 to C 30 alkyl (akyl)) 15 (selected from the group consisting of) It is represented by a formula selected from the following. In some embodiments, the aromatic diol is selected from the group consisting of 1,3-dihydroxybenzene, 1,4-dihydroxybenzene, 2,5-biphenyldiol, 4,4'-biphenol, 4,4'-(propane-2,2-diyl)diphenol, 4,4'-(ethane-1,2-diyl)diphenol, 4,4'-methylenediphenol, bis(4-hydroxyphenyl)methanone, 4,4'-oxydiphenol, 4,4'-sulfonyldiphenol, 4,4'-thiodiphenol, naphthalene-2,6-diol, and naphthalene-1,5-diol. Preferably, the aromatic diol is 4,4'-biphenol.
[0020] In some embodiments, the first aromatic dicarboxylic acid is from the group of the following formulas: HOOC-Ar1-COOH, and (3) HOOC-Ar2-T2-Ar3-COOH, (4) (In the formula, Ar1 to Ar3 are given as above and selected independently; T2 is selected from the bonds, O and S.) It is independently represented by a formula selected from the following. In some embodiments, the first aromatic dicarboxylic acid is selected from the group consisting of isophthalic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-oxydibenzoic acid, 4,4'-(ethylenedioxy)dibenzoic acid, 4,4'-sulfandiyldibenzoic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, and naphthalene-2,3-dicarboxylic acid. Preferably, the first aromatic dicarboxylic acid is selected from the group consisting of isophthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, and naphthalene-2,3-dicarboxylic acid. Most preferably, the first aromatic dicarboxylic acid is isophthalic acid.
[0021] In some embodiments, aromatic hydroxycarboxylic acids are HO-Ar1-COOH, and (5) HO-Ar2-Ar3-COOH, (6) (In the formula, Ar1 to Ar3 are given above and can be selected independently.) It is represented by a formula selected from the group consisting of 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 6-hydroxy-1-naphthoic acid, 2-hydroxy-1-naphthoic acid, 3-hydroxy-2-naphthoic acid, 1-hydroxy-2-naphthoic acid, 5-hydroxy-1-naphthoic acid, and 4'-hydroxy-[1,1'-biphenyl]-4-carboxylic acid. Preferably, the aromatic hydroxycarboxylic acid is selected from the group consisting of 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 6-hydroxy-1-naphthoic acid, 2-hydroxy-1-naphthoic acid, 3-hydroxy-2-naphthoic acid, 1-hydroxy-2-naphthoic acid, and 5-hydroxy-1-naphthoic acid. Most preferably, the aromatic hydroxycarboxylic acid is 4-hydroxybenzoic acid.
[0022] In some embodiments, the LCP formed from the aforementioned monomers is a repeating unit R LCP1 ~R LCP4 It has a repeating unit R. LCP1 The formula is as follows: [ka] Repeating unit R LCP2 The formula is as follows: -[-O-Ar1-O-]-, and (8) -[-O-Ar2-T1-Ar3-O-]-;(9) It is represented by one of the following: Repeating unit R LCP3 The formula is as follows: -[-OC-Ar1-CO-]-, and (10) -[-OC-Ar2-T2-Ar3-CO-]-; and (11) It is represented by one of the following: Repeating unit R LCP4 The formula is as follows: -[-O-Ar1-CO-]-, and (12) -[-O-Ar2-Ar3-CO-]-(13) It is represented by one of the following: In the formula, Ar1 to Ar3, T1 and T2 are given above and are selected independently. Those skilled in the art will know that R according to formula (7) LCP1 R is formed from terephthalic acid; R according to formulas (8) and (9) LCP2 However, they are formed from monomers according to formulas (1) and (2), respectively; and R according to formulas (10) and (11). LCP3 However, they are formed from monomers according to formulas (3) and (4), respectively; and R according to formulas (12) and (13). LCP4 However, it will be recognized that it is formed from monomers according to formulas (5) and (6). Thus, the selection of Ar1 to Ar3, T1 and T2 for monomers of formulas (1) to (6) is also the repeating unit R LCP2 ~R LCP4 Select Ar1 to Ar3, T1 and T2 for the following. Preferably, the repeating unit R LCP1 ~R LCP4 These are formed from the polycondensation of terephthalic acid, 4,4'-biphenol, isophthalic acid, and 4-hydroxybenzoic acid, respectively.
[0023] In some embodiments, the repeating unit R LCP1 ~R LCP4 The total concentration is at least 50 mol%, at least 60 mol%, at least 70 mol%, at least 80 mol%, at least 90 mol%, at least 95 mol%, at least 99 mol%, or at least 99.9 mol%. In some embodiments, the concentration of terephthalic acid is 5 mol% to 30 mol%, preferably 10 mol% to 20 mol%. In some embodiments, the concentration of aromatic diol is 10 mol% to 30 mol%, preferably 15 mol% to 25 mol%. In some embodiments, the concentration of the first aromatic dicarboxylic acid is 1 mol% to 20 mol%, preferably 1 mol% to 10 mol%. In some embodiments, the concentration of aromatic hydrocarboxylic acid is 35 mol% to 80 mol%, preferably 45 mol% to 75 mol%, most preferably 50 mol% to 17 mol%. In some embodiments, R LCP1 ~RLCP4 These are derived from terephthalic acid, 4,4'-biphenol, isophthalic acid, and 4-hydroxybenzoic acid, respectively, where the concentration range for each repeating unit is within the range given above. As used herein, the mole percent of each repeating unit is relative to the total number of moles of repeating units in the polymer unless otherwise specified. For clarity, "derived from" refers to repeating units formed from the polycondensation of the enumerated monomers, for example, as described above with respect to the relationship between formulas 1-6 and 8-13.
[0024] In some embodiments, the LCP has a Tm of at least 310°C, at least 320°C, or at least 330°C. In some embodiments, the LCP has a Tm of 390°C or less, 380°C or less, or 370°C or less. In some embodiments, the LCP has a Tm of 310°C to 390°C, 320°C to 380°C, or 330°C to 370°C.
[0025] In some embodiments, LCP has a number-average molecular weight ("Mn") of at least 5,000 g / mol. In some embodiments, LCP has an Mn of 20,000 g / mol or less. In some embodiments, LCP has an Mn of 5,000 g / mol to 20,000 g / mol. The number-average molecular weight Mn can be measured by gel permeation chromatography (GPC) according to ASTM D5296 and using hexafluoropropanol solvent and a poly(methyl methacrylate) standard.
[0026] In some embodiments, the LCP concentration in the polymer composition is at least 20% by weight, at least 30% by weight, at least 35% by weight, or at least 40% by weight. In some embodiments, the LCP concentration in the polymer composition is 80% by weight or less, 75% by weight or less, or 70% by weight or less. In some embodiments, the LCP concentration in the polymer composition is 30% to 80% by weight, 30% to 75% by weight, or 30% to 70% by weight. In some embodiments, the LCP concentration in the polymer composition is 35% to 80% by weight, 35% to 75% by weight, or 35% to 70% by weight. In some embodiments, the LCP concentration in the polymer composition is 40% to 80% by weight, 40% to 75% by weight, or 40% to 70% by weight.
[0027] The LCPs described herein can be prepared by any conventional method adapted to the synthesis of LCPs.
[0028] Boron nitride or zinc oxide The polymer composition comprises boron nitride and / or zinc oxide. In some embodiments, the polymer composition comprises either boron nitride or zinc oxide. In one such embodiment, the polymer composition comprises boron nitride but does not contain zinc oxide. In other embodiments, the polymer composition comprises zinc oxide but does not contain boron nitride. In some embodiments, the polymer composition comprises both boron nitride and zinc oxide. As used herein and unless otherwise specified, "free of" a component means that the concentration of the component in the polymer composition is 1% by weight or less, 0.5% by weight or less, 0.1% by weight or less, or 0.05% by weight or less.
[0029] The total concentration of boron nitride and zinc oxide in the polymer composition is 15% to 50% by weight. In some embodiments, the total concentration of boron nitride and zinc oxide is at least 20% by weight. In some embodiments, the total concentration of boron nitride and zinc oxide is 45% or less by weight or 40% or less by weight. In some embodiments, the total concentration of boron nitride and zinc oxide is 15% to 45% by weight or 15% to 40% by weight. In some embodiments, the total concentration of boron nitride and zinc oxide is 20% to 50% by weight, 20% to 45% by weight or 20% to 40% by weight. In embodiments containing both boron nitride and zinc oxide, the relative concentration of boron nitride to zinc oxide (weight of boron nitride in the polymer composition / weight of zinc oxide in the polymer composition) is 0.5 to 2, 0.75 to 1.3, 0.80 to 1.2, or 0.90 to 1.1. In embodiments comprising either boron nitride or zinc oxide, the boron nitride concentration or the zinc oxide concentration is within the same range as provided above for the total concentrations of boron nitride and zinc oxide, respectively.
[0030] Flat glass fiber The polymer composition further comprises flattened glass fibers. The glass fibers are silica-based glass compounds containing several metal oxides that can be adjusted to yield various types of glass. The main oxide is silica in the form of silica sand, and other oxides such as calcium, sodium, and aluminum are incorporated to lower the melting temperature and prevent crystallization. The glass fibers can be added as endless fibers or chopped glass fibers. All types of glass fibers, such as A, C, D, E, M, S, R, and T glass fibers (described in Chapter 5.2.3, pp. 43-48 of Additives for Plastics Handbook, 2nd ed., John Murphy), or any mixture thereof or mixtures thereof can be used. For example, R, S, and T glass fibers are typically high-modulus glass fibers having an elastic modulus of at least 76, preferably at least 78, more preferably at least 80, and most preferably at least 82 GPa as measured according to ASTM D2343.
[0031] E, R, S, and T glass fibers are well known in the art. They are described in particular in Fiberglass and Glass Technology, Wallenberger, Frederick T.; Bingham, Paul A. (Eds.), 2010, XIV, chapter 5, pages 197-225. R, S, and T glass fibers are essentially composed of silicon, aluminum, and magnesium oxides. In particular, these glass fibers typically contain 62-75% by weight of SiO2, 16-28% by weight of Al2O3, and 5-14% by weight of MgO, based on the total weight of the glass fiber. In contrast to ordinary E-glass fibers, which are widely used in polymer compositions, R, S, and T glass fibers contain less than 10% by weight of CaO.
[0032] Generally, glass fibers have an aspect ratio defined as the average ratio between the length and the maximum width and thickness, of at least 5, at least 10, at least 20, or at least 50. In some embodiments, the glass fibers have an average length of 3 mm to 50 mm. In some such embodiments, the glass fibers have an average length of 3 mm to 10 mm, 3 mm to 8 mm, 3 mm to 6 mm, or 3 mm to 5 mm. In alternative embodiments, the glass fibers have an average length of 10 mm to 50 mm, 10 mm to 45 mm, 10 mm to 35 mm, 10 mm to 30 mm, 10 mm to 25 mm, or 15 mm to 25 mm. The average length of the glass fibers can be considered as the average length of the glass fibers before they are incorporated into the polymer composition or as the average length of the glass fibers within the polymer composition.
[0033] Flattened glass fibers are glass fibers that have a non-circular cross-section, such as oval, elliptical, or rectangular.
[0034] In some embodiments, the glass fiber has a maximum cross-sectional diameter of at least 15 μm, preferably at least 20 μm, more preferably at least 22 μm, and even more preferably at least 25 μm. Further or alternatively, in some embodiments, the glass fiber has a maximum cross-sectional diameter of up to 40 μm, preferably at least 35 μm, more preferably at least 32 μm, and even more preferably at least 30 μm. In some embodiments, the glass fiber has a maximum cross-sectional diameter of 15 μm to 35 μm, preferably at least 20 μm to 30 μm, and more preferably at least 25 μm to 29 μm. In some embodiments, the glass fiber has a minimum cross-sectional diameter of at least 4 μm, preferably at least 5 μm, more preferably at least 6 μm, and even more preferably at least 7 μm. Further or alternatively, in some embodiments, the glass fiber has a minimum cross-sectional diameter of up to 25 μm, preferably at least 20 μm, more preferably at least 17 μm, and even more preferably at least 15 μm. In some embodiments, the glass fiber has a minimum cross-sectional diameter of 5 μm to 20 μm, preferably 5 μm to 15 μm, and more preferably 7 μm to 11 μm. In some embodiments, the glass fiber has an aspect ratio of at least 2, preferably at least 2.2, more preferably at least 2.4, and even more preferably at least 3. The aspect ratio is defined as the ratio of the longest diameter in the cross-section of the glass fiber to its shortest diameter. In some embodiments, the glass fiber has an aspect ratio of up to 8, preferably at least 6, and more preferably at least 4. In some embodiments, the glass fiber has an aspect ratio of 2 to 6, preferably 2.2 to 4.
[0035] The cross-sectional shape, length, diameter, and aspect ratio of glass fibers can be easily determined using optical microscopy. For example, the aspect ratio of a fiber cross-section can be determined by measuring the longest (width) and shortest (height) dimensions of the fiber cross-section using a Euromex optical microscope and image analysis software (Image Focus 2.5), and then dividing the first number by the second number.
[0036] In some embodiments, the glass fibers have an elastic modulus of at least 76 GPa, preferably at least 78, more preferably at least 80, even more preferably at least 82, and most preferably at least 84 GPa, as measured according to ASTM C1557-03. In some embodiments, the glass fibers have a tensile strength of at least 3.5 GPa, preferably at least 3.6, more preferably at least 3.7, even more preferably at least 3.8, and most preferably at least 3.9 GPa, as measured according to ASTM C1557-03. These levels of elastic modulus and tensile strength are typically achieved when using a specific chemical composition of glass used to produce glass fibers. Glass is a silica-based glass compound containing several metal oxides that can be adjusted to produce different types of glass. The main oxide is silica in the form of silica sand, and other oxides such as calcium, sodium, and aluminum are introduced to lower the melting temperature and prevent crystallization. It is well known in the art that when using glass with a high Al2O3 load, the glass fibers derived therefrom exhibit a high elastic modulus. In particular, these glass fibers typically contain 55-75% by weight of SiO2, 16-28% by weight of Al2O3, and 5-14% by weight of MgO, based on the total weight of the glass composition. In contrast to ordinary E-glass fibers, which are widely used in polymer compositions, high-modulus glass fibers contain less than 5% by weight, preferably less than 1% by weight of B2O3, based on the total weight of the glass composition.
[0037] The concentration of flattened glass fibers in the polymer composition is 10% to 40% by weight. In some embodiments, the concentration of flattened glass fibers in the polymer composition is 10% to 35% by weight, 10% to 30% by weight, 15% to 40% by weight, 15% to 35% by weight, or 15% to 30% by weight, based on the total weight of the polymer composition.
[0038] additives In some embodiments, the polymer composition also includes additives selected from the group consisting of additional reinforcing agents, strengthening agents, plasticizers, colorants, pigments, antistatic agents, dyes, lubricants, heat stabilizers, light stabilizers, flame retardants, nucleating agents, and antioxidants.
[0039] A wide range of additional reinforcing agents can be added to the polymer composition. These additional reinforcing agents can be selected from fibrous reinforcing agents and particulate reinforcing agents. A fibrous reinforcing agent is considered herein to be a material having length, width, and thickness such that the average length is significantly greater than both the width and thickness. Generally, such a material has an aspect ratio defined as the average ratio between the length and the maximum width and thickness, at least 5, at least 10, at least 20, or at least 50. In some embodiments, the fibrous reinforcing agent has an average length of 3 mm to 50 mm. In some such embodiments, the fibrous reinforcing agent has an average length of 3 mm to 10 mm, 3 mm to 8 mm, 3 mm to 6 mm, or 3 mm to 5 mm. In alternative embodiments, the fibrous reinforcing agent has an average length of 10 mm to 50 mm, 10 mm to 45 mm, 10 mm to 35 mm, 10 mm to 30 mm, 10 mm to 25 mm, or 15 mm to 25 mm. The average length of the fiber reinforcement can be interpreted as the average length of the fiber reinforcement before incorporation into the polymer composition, or as the average length of the fiber reinforcement within the polymer composition. Examples of fiber reinforcements include, but are not limited to, additional glass fibers (e.g., circular glass fibers), carbon fibers, synthetic polymer fibers, aramid fibers, aluminum fibers, titanium fibers, magnesium fibers, boron carbide fibers, rock wool fibers, and steel fibers. Circular glass fibers are glass fibers having a substantially circular cross-section (e.g., a cross-section with different vertical axes within the cross-section, with lengths of less than 5%, less than 1%, or less than 0.5%). Examples of granular reinforcements include, but are not limited to, talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate, and wollastonite.
[0040] In some embodiments, the concentration of the reinforcing agent in the polymer composition is at least 15% by weight, at least 20% by weight, at least 25% by weight, or at least 30% by weight. In some embodiments, the concentration of the reinforcing agent is 45% by weight or less. In some embodiments, the concentration of the reinforcing agent is 20% to 45% by weight, or 30% to 45% by weight.
[0041] In some embodiments, the polymer composition does not contain reinforcing agents. In some embodiments, the polymer composition does not contain additional glass fibers. In some embodiments, the polymer composition does not contain circular glass fibers. With respect to reinforcing agents (e.g., additional glass fibers or circular glass fibers), "free of" means that the concentration of reinforcing agents is less than 10% by weight, less than 5% by weight, less than 1% by weight, or less than 0.5% by weight.
[0042] The polymer composition may also contain a reinforcing agent. The reinforcing agent is generally a low glass transition temperature (Tg) polymer, such as one with a Tg below room temperature, below 0°C, or even below -25°C. As a result of its low Tg, the reinforcing agent is typically elastomeric at room temperature. The reinforcing agent may be a functionalized polymer backbone.
[0043] The polymer backbone of the reinforcing agent can be selected from elastomeric backbones containing polyethylene and its copolymers, e.g., ethylene-butene, ethylene-octene; polypropylene and its copolymers; polybutene; polyisoprene; ethylene-propylene rubber (EPR); ethylene-propylene-diene monomer rubber (EPDM); ethylene-acrylate rubber; butadiene-acrylonitrile rubber, ethylene-acrylic acid (EAA), ethylene-vinyl acetate (EVA); acrylonitrile-butadiene-styrene rubber (ABS), block copolymer styrene-ethylene butadiene styrene (SEBS), block copolymer styrene-butadiene styrene (SBS); methacrylate-butadiene styrene (MBS) type core-shell elastomers, or mixtures of one or more of the above.
[0044] If the reinforcing agent is functionalized, the functionalization of the main chain can result from copolymerization of monomers containing the functionalization or from grafting of the polymer main chain with further components.
[0045] Specific examples of functionalized reinforcing agents include, among others, terpolymers of ethylene, acrylic acid esters, and glycidyl methacrylate; copolymers of ethylene and butyl ester acrylate; copolymers of ethylene, butyl ester acrylate, and glycidyl methacrylate; ethylene-maleic anhydride copolymer; EPR grafted with maleic anhydride; styrene copolymer grafted with maleic anhydride; SEBS copolymer grafted with maleic anhydride; styrene-acrylonitrile copolymer grafted with maleic anhydride; and ABS copolymer grafted with maleic anhydride.
[0046] In some embodiments, the concentration of the reinforcing agent is at least 1% by weight, at least 2% by weight, or at least 3% by weight. Furthermore, or alternatively, in some embodiments, the concentration of the reinforcing agent is 30% by weight or less, 20% by weight or less, 15% by weight or less, or 10% by weight or less.
[0047] The polymer composition may also include other conventional additives commonly used in the art, such as plasticizers, colorants, pigments (e.g., black pigments such as carbon black and nigrosine), antistatic agents, dyes, lubricants (e.g., linear low-density polyethylene, calcium or magnesium stearate, or sodium montanoate), heat stabilizers, light stabilizers, flame retardants, nucleating agents, and antioxidants.
[0048] Preparation of polymer compositions Polymer compositions can be prepared by melt-blending LCP and specific components (e.g., flattened glass fibers and boron nitride or zinc oxide), as well as any other additives.
[0049] The polymer and nonpolymer components may be mixed using any suitable melt-blending method known in the art. For example, the polymer and nonpolymer components can be fed into a melt mixer such as a single-screw or twin-screw extruder, a stirrer, a single-screw or twin-screw kneader, or a Banbury mixer, and the addition step may be simultaneous addition of all components or batch-type stepwise addition. When the polymer and nonpolymer materials are added gradually in a batch type, a portion of the polymer and / or nonpolymer materials are added first, and then melt-mixed with the remaining polymer and nonpolymer materials to be added thereafter until a well-mixed composition is obtained. If the reinforcing material has a long physical shape (e.g., long glass fibers), stretch extrusion may be used to prepare the reinforced composition.
[0050] Articles and Uses The polymer composition can preferably be incorporated into an article. This article can be used, in particular, in application environments where thin-walled articles are formed (e.g., by injection molding) from the polymer composition.
[0051] As used herein, a thin-walled article is an article having a portion with a maximum thickness of 1 mm or less, 0.9 mm or less, 0.8 mm or less, or 0.7 mm or less (along a line perpendicular to the surface on which the measurement is taken). Preferably, this portion has an area of at least 1 mm 2 , at least 10mm 2 , at least 100mm 2 , or at least 1000mm 2 It is a region on the surface of an article.
[0052] In some embodiments, the article is an automotive, aerospace, or marine component (including, but not limited to, ships and jet skis). In some embodiments, including, but not limited to, those described above, the article is an electrical component (e.g., an electric vehicle component). In some embodiments, the electrical component is in contact with or includes a current carrier. In some embodiments, including, but not limited to, those described above, the article is an electric motor component (e.g., an electric vehicle motor component). In some embodiments, the article is a slot liner. The slot liner is incorporated into the stator or rotor of an electric motor (including a generator). The slot liner provides insulation between the stator core or motor core and the stator windings or rotor windings, respectively. As described above, the polymer compositions described herein are particularly desirable for high-power-density motor applications, at least due to their significantly improved per-plane thermal conductivity. For clarity, the articles described above may be thin-walled or non-thin-walled articles. Preferably, the articles are thin-walled articles.
[0053] Melt extrusion involves the process of extruding a molten polymer or polymer composition through a die or orifice. The molten polymer can be formed during melt blending, as described above, or it can be formed by melting a polymer or polymer composition that has been pre-formed, for example, in the form of pellets. For injection molding applications, the molten polymer is pushed into a mold, where it solidifies, and then removed (removed from the mold). In some embodiments where the molten polymer is formed by melt blending (e.g., extrusion), the mold can be directly or indirectly connected to a melt blending device (e.g., an extruder) so that the polymer composition is pushed into the mold before it cools significantly. In other embodiments, solid pellets of the polymer or polymer composition can be melted, and the melting device can be directly or indirectly connected to the mold so that the molten polymer or polymer composition can be supplied into the mold. The mold corresponds to the shape of the article to be formed. As described above, the polymer composition has a melt viscosity that is particularly desirable for injection molding applications for thin-walled articles formed by injection molding.
[0054] Articles can be printed from a polymer composition by a process including the step of extruding the material, for example, in the form of a filament, or by a process including the step of laser sintering the material, in this case in the form of a powder.
[0055] A method for manufacturing a three-dimensional (3D) object using an additive manufacturing system is also provided, comprising the steps of providing a component material containing a polymer composition and printing layers of a three-dimensional object from the component material.
[0056] The polymer composition may therefore be in the form of threads or filaments used in 3D printing processes, such as fused deposition modeling ("FDM"), also known as fused filament manufacturing methods.
[0057] The polymer composition may also be in the form of a powder, such as substantially spherical powder, used in 3D printing processes, such as selective laser sintering (SLS).
[0058] If any disclosure of any patent, patent application, or publication incorporated herein by reference is inconsistent with the description of this application to such an extent that it obscures the terminology, the description herein shall prevail. [Examples]
[0059] The following examples demonstrate the film-forming ability, dielectric properties, and mechanical properties of this polymer composition. The following raw materials were used in the examples: - LCP: A liquid crystal polymer formed from the following monomers: isophthalic acid; terephthalic acid; 4,4'-biphenol; and p-hydroxybenzoic acid. - Flattened glass fibers ("FGF"): Commercially obtained from Nitto Boseki Co., LTD (CSG 3PA-830). - Circular glass fibers ("RGF"): Commercially obtained from Saint-Gobain (910). - Lubricant: Commercially obtained from Solvay Specialty Polymers Italy, SpA under the trade name Polymist (registered trademark) F5A. - Boron nitride: Commercially obtained from Momentive (CF600 Boron Nitride). - Zinc oxide: Commercially obtained from Dryteck (Pana-Tetra).
[0060] Example 1: Synthesis of LCP and Formation of Sample To synthesize LCP, dicarboxylic acid monomers (terephthalic acid (167.0 g, Flint Hills Resources), isophthalic acid (55.7 g, Lotte Chemicals), p-hydroxybenzoic acid (555.5 g, Sanfu), 4,4'-biphenol (201.6 g, SI Group), and acetic anhydride (769.2 g, Aldrich)) were charged into a 2 L glass reactor. Potassium acetate (0.07 g, Aldrich) and magnesium acetate (0.2 g, Aldrich) were used as catalysts. The mixture was heated to 165°C, and the acetylation reaction was carried out under reflux conditions for 1 hour. Then, heating was continued at a rate of 0.5°C per minute to 300°C while acetic acid was distilled off from the reactor. The prepolymer was discharged and allowed to cool. The material was then ground into a powder for solid-phase polymerization. The resin was subjected to the following profile: continuous nitrogen purging at 220°C for 1 hour, 290°C for 1 hour, and 310°C for 12 hours. The resulting high molecular weight resin had a melt viscosity of 60-140 Pa-s at 370°C.
[0061] The samples were formed by melt-blending the polymer composition in an extruder and then cut into pellets. Samples for heating / cooling tests, mechanical tests, and physical tests were formed by injection molding. Sample parameters are shown in Table 1. All values in Table 1 are in weight percent and are based on the total weight of the polymer composition.
[0062] [Table 1]
[0063] Example 2: Thermal performance, mechanical performance, and rheological performance This example demonstrates the thermal, mechanical, and rheological properties of the sample.
[0064] To demonstrate thermal performance, through-surface conductivity was measured using a Netzsch LFA467 hyperflash instrument and by the flash method according to ASTM E1461-13, “Standard Test Method for Thermal Diffusivity by the Flash Method”. To demonstrate mechanical performance, bending strength and bending strain were measured according to ASTM D790. To demonstrate rheological performance, η (apparent viscosity) was measured according to ASTM D3835. The results for thermal, mechanical, and rheological performance are shown in Table 2.
[0065] [Table 2]
[0066] Samples containing a combination of flattened glass fibers and boron nitride exhibited improved per-plane conductivity, flexural strength at fracture, and flexural strain at fracture compared to samples containing a combination of rounded glass fibers and boron nitride. Referring to Table 2, a comparison of C1 and E4 demonstrates that the addition of boron nitride (E4) to the LCP composition containing flattened glass fibers results in a per-plane conductivity of 0.38 W / mK, representing an improvement of approximately 90% compared to a similar LCP composition without boron nitride (C1). A comparison of C2 and C3 demonstrates that the addition of boron nitride (C3) to the LCP composition containing rounded glass fibers results in a per-plane conductivity of only approximately 0.35 W / mK, which is lower than the per-plane conductivity of E4 and represents an improvement of only approximately 21% compared to a similar LCP composition without boron nitride (C2). Furthermore, the addition of boron nitride E4 to C1 and C3 to C2 reduces the flexural strength and flexural strain at fracture, but E4 exhibits improved flexural strength and flexural strain at fracture compared to C3.
[0067] Similarly, samples with a combination of flattened glass fibers and zinc oxide exhibited improved per-plane conductivity, flexural strength at fracture, and flexural strain at fracture compared to samples with a combination of rounded glass fibers and zinc oxide. Referring to Table 2, a comparison of C1 and E5 demonstrates that the addition of zinc oxide to the LCP composition with flattened glass fibers (E5) resulted in a per-plane conductivity of 0.25 W / mK, representing an improvement of approximately 25% compared to a similar LCP composition without zinc oxide (C1). A comparison of C2 and C4 demonstrates that the addition of zinc oxide to the LCP composition with rounded glass fibers (C4) resulted in a per-plane conductivity of only approximately 0.24 W / mK, which is slightly lower than the per-plane conductivity of E4 and represents a decrease of approximately 17% compared to a similar LCP composition without zinc oxide (C2).
[0068] Furthermore, the addition of zinc oxide E5 to C1 and C4 to C2 reduces the flexural strength and flexural strain at fracture, but E5 exhibits improved flexural strength and flexural strain at fracture compared to C4. Furthermore, samples containing both flattened glass fibers and boron nitride and zinc oxide exhibited improved bending properties while maintaining excellent permeable conductivity compared to samples containing only flattened glass fibers and boron nitride. Referring to Table 2, a comparison of E1 and E6 demonstrates that the former had higher permeable conductivity, while the latter had significantly improved bending strength at fracture and improved bending strain at fracture.
[0069] The embodiments described above are illustrative and not limiting. Additional embodiments are within the concept of the present invention. In addition, while descriptions of specific embodiments are provided, those skilled in the art will recognize that modifications in form and detail may be made without departing from the spirit and scope of the invention. Any use by reference to the above-mentioned documents is limited so as not to use subject matter contrary to the express disclosure herein.
Claims
1. - at least 20% by weight of a liquid crystal polymer ("LCP") formed from the polycondensation of the following monomers: terephthalic acid, 4,4'-biphenol, isophthalic acid, and 4-hydroxybenzoic acid; - 10% to 40% by weight of flat glass fibers, boron nitride and zinc oxide, the total concentration of boron nitride and zinc oxide being between 15% and 50% by weight, - optional additives selected from the group consisting of tougheners, plasticizers, colorants, pigments, antistatic agents, dyes, lubricants, heat stabilizers, light stabilizers, nucleating agents, and antioxidants; A polymer composition comprising: the relative concentration of boron nitride to zinc oxide, expressed as weight of boron nitride in the polymer composition / weight of zinc oxide in the polymer composition, is from 0.5 to 2; Polymer composition.
2. 10. The polymer composition of claim 1 having a through-plane thermal conductivity of 0.20 W / mK to 0.9 W / mK, measured by laser flash according to ASTM E1461-13.
3. 3. The polymer composition according to claim 1 or 2, having a flexural strength according to ASTM D790 of 100 MPa to 250 MPa.
4. 3. The polymer composition of claim 1 or 2, having a flexural strain measured according to ASTM D790 of from 100 MPa to 190 MPa.
5. Measured according to ASTM D3835, 100s -1 At shear rates of 90 Pa·s to 300 Pa·s, 500 s -1 At a shear rate of 35 Pa·s to 150 Pa·s, or 1000 s -1 3. The polymer composition according to claim 1, having an apparent viscosity of from 25 Pa·s to 100 Pa·s at a shear rate of 100 Pa·s.
6. The polymer composition of claim 1, wherein the concentration of the flat glass fibers is from 10% by weight to 30% by weight based on the total weight of the polymer composition.
7. The polymer composition of claim 1, wherein the glass fibers have an aspect ratio, defined as the average ratio between the length and the maximum of the width and thickness, of at least 5.